GE_GERICHTE P/17644/2014 vom 30. September 2016 - GE Cour de justice (2016)
LÉSION CORPORELLE GRAVE ; VOL(DROIT PÉNAL) ; ASTUCE ; RÉGIME DE LA DÉTENTION ; TORT MORAL | CP122; CP15; CP16; CP139; CP89.1; CEDH3; CO47